ANALISIS PENGGUNAAN METODE STORYTELLING DALAM PEMBELAJARAN BAHASA INDONESIA TERHADAP KEMAMPUAN BERBICARA SISWA - Azman, Muhammad; Bakhtiar, Afakhrul Masub (Universitas Negeri Medan, 2024)
Storytelling has become a significant approach in Indonesian language learning, focusing on developing students' speaking skills. In this context, research and literature analysis show that storytelling is not just a tool for delivering stories but also an effective means of training students to communicate effectively. The various benefits of using storytelling methods in the context of Indonesian language learning. These findings indicate that storytelling methods can improve students' speaking abilities in various ways, including improving vocabulary, grammar, pronunciation, increasing emotional engagement, dynamic interaction between teachers and students, developing critical and creative thinking, and boosting students' confidence. Therefore, implementing storytelling methods in Indonesian language learning is an important and beneficial step in developing students' speaking skills comprehensively. This underscores the importance of innovative approaches and student-oriented experiences in improving language learning outcomes. Thus, further research and practice in using storytelling methods in the context of Indonesian language learning are expected to make a meaningful contribution to enhancing the quality of language education in Indonesia.